2021
DOI: 10.15252/embj.2020106393
|View full text |Cite
|
Sign up to set email alerts
|

Phf5a regulates DNA repair in class switch recombination via p400 and histone H2A variant deposition

Abstract: Antibody class switch recombination (CSR) is a locus-specific genomic rearrangement mediated by switch (S) region transcription, activation-induced cytidine deaminase (AID)-induced DNA breaks, and their resolution by non-homologous end joining (NHEJ)-mediated DNA repair. Due to the complex nature of the recombination process, numerous cofactors are intimately involved, making it important to identify rate-limiting factors that impact on DNA breaking and/or repair. Using an siRNA-based loss-of-function screen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Some previous studies have demonstrated that H2A.Z was shown to interact with components of complexes involved in a multitude of biological processes, such as DNA damage repair [ 26 ], gene activation [ 27 ], gene repression [ 28 ], various transcription factors [ 29 31 ], and chromatin remodeling [ 32 ]; however, the underlying mechanism of action remains unclear in ICC. Using the STRING database, we identified potential molecules that interact with H2A.Z (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have demonstrated that H2A.Z was shown to interact with components of complexes involved in a multitude of biological processes, such as DNA damage repair [ 26 ], gene activation [ 27 ], gene repression [ 28 ], various transcription factors [ 29 31 ], and chromatin remodeling [ 32 ]; however, the underlying mechanism of action remains unclear in ICC. Using the STRING database, we identified potential molecules that interact with H2A.Z (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 A and Fig. S 2 A show, the downregulation of HP1α can decrease H3K9me3 enrichment and the DNA methylation rate in the P1 region (-116 ~ + 1 bp) of the SFRP1 promoter, resulting in the increase of SFRP1 expression [ 26 ]. In order to explore whether H2A.Z, similar to HP1α, affects SFRP1 expression by influencing the histone methylation level and DNA methylation rate of the SFRP1 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…How AID regulates the mechanistically distinct processes of S region DNA double strand breaks and S-S synapse formation remains poorly understood (69). While numerous AID-interacting and non-interacting CSR regulatory factors have been identified, these factors appear to play exclusive roles in either DNA break, repair, or synapse formation (4,(70)(71)(72)(73)(74). Here, we show Med12 is a novel CSR cofactor that not only promotes AID-induced DNA double strand breaks and synapse formation but also supports DNA repair via NHEJ (Fig.…”
Section: Depletion Of 3'rr Ernas Perturbs Enhancer Function and Impai...mentioning
confidence: 99%
“…DNA recombination [ 37 39 ] refers to the recombination of DNA fragments from different sources to disrupt the original DNA sequence. For example, the two DNA double strands intercept a 4-base DNA fragment at the end, and recombine the two DNA fragments with the original DNA strand to obtain two DNA strands that are different from the original.…”
Section: Basic Principlesmentioning
confidence: 99%
“…DNA recombination technology [ 37 39 ] refers to the use of artificial means to recombine DNA fragments with a certain special meaning from different sources to achieve the purpose of changing biological characteristics. In this paper, DNA recombination technology is introduced into DNA encryption, and arbitrary fragments are changed by artificial means.…”
Section: Introductionmentioning
confidence: 99%